(untitled) (Bioscience Journal, 2016)
Violence becomes a matter to be discussed in the health-disease process, once it reaches the collective and individual health, requiring action and articulation of services. Suicide is the third leading cause of death in Brazil, however, these self-extermination attempts are not being successfully reported (undernotified) and, sometimes, not even reported at all. To characterize the cases of self-extermination attempt in the emergency department of a university hospital. This was a retrospective, cross-sectional study with a quantitative approach. Â 162 medical records were included in self-extermination attempt cases, for the period from January 2008 to September 2013. From the 162 analyzed records, 56.17% were women; 22.22% within the age group between 24 and 38 years old, average age of 34.5 years old; 53.09% single; 94.44% coming from Uberlândia. 39.51% occurred at night; frequency of 19.14% on Mondays; 24.68% of attempts in 2012. Abusive ingestion of medications in 34.07% of cases; 51.23% were brought to the hospital by the Fire Department; 35.83% had a mental disorder; 45.67% of the cases were the patient’s first attempt; 39.42% of cases occurred after relationship conflicts. 54.32% were discharged within 18 hours, on average, after care in the emergency room; 21.60% have returned because of a new attempt. The research was characterized attempts at self-extermination cases, with predominantly female, aged between 24 and 38, use of medication as an agent to act, with high recidivism among the female group. It is suggested research with longer periods and samples and analyzed by The National Policy for Reduction of Morbidity and Mortality by Accidents and Violence.